Finite element analysis of a reconstructed pulmonary conduit with valve - Kua, Joel Zi Xiang. (2012)
It is found that bioprosthetic aortic valves which have the advantage of avoiding anticoagulation have been implanted extensively in the recent years. For this reason, there is a high interest in designing a bioprosthetic aortic valve that is not only truly stentless yet also simple and fast for surgeon to implant. The current use of aortic valve replacement mainly comes in tricuspid design and the approach of reconstruction of aortic valve is relatively new. Although it is believed that leaflet design which resembles the native valve exerts a positive influence on the mechanical performance, there is also substantial evidence that the leaflet geometry plays an important role for the efficacy and durability of the bioprosthetic valve. Therefore, research and development of simpler and better designs of bioprosthetic aortic valve is applicable with today’s technology.